CORRELATION OF INSULIN RESISTANCE WITH SEVERITY OF OBSTRUCTIVE SLEEP APNOEA - Dr. Chinthu Sara Jacob; Dr. P.G. Vijayamohanan; Dr. Suresh D.; Dr. Bhaskar M.K. (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: OSA, or obstructive sleep apnea, is a common but underdiagnosed sleep disorder in which the upper airway gets blocked during sleep, causing periods of low oxygen, sleep fragmentation, and being too sleepy during the day. It has been strongly associated with metabolic disorders, including IR (Insulin Resistance), a key factor in the pathogenesis of type 2 diabetes mellitus and metabolic syndrome. While various studies have postulated a correlation between OSA severity and insulin resistance, conflicting findings necessitate further investigation. This study aims to evaluate the relationship between the severity of OSA and insulin resistance using polysomnographic data and metabolic parameters. Methods: A hospital-based cross-sectional study was conducted on 60 patients diagnosed with OSA through overnight PSG (Polysomnography). The severity of OSA was classified based on the AHI (Apnea-Hypopnea Index) into mild, moderate, and severe categories. Fasting blood glucose and insulin levels were measured to calculate the HOMA-IR (Homeostasis Model Assessment of Insulin Resistance). Statistical analysis was performed to assess the correlation between OSA severity and insulin resistance, with a p-value <0.05 considered significant. Results: A significant correlation was observed between increasing OSA severity and higher HOMA-IR values, suggesting a positive association between OSA and insulin resistance. Severe OSA cases demonstrated significantly higher fasting insulin levels and HOMA-IR indices compared to mild and moderate OSA groups. However, no significant association was found between BMI (Body Mass Index) and insulin resistance, indicating that OSA may contribute to metabolic dysfunction independently of obesity. Conclusion: The study highlights a significant association between OSA severity and insulin resistance, supporting the hypothesis that OSA is an independent risk factor for metabolic dysfunction. These findings emphasize the need for early screening and management of insulin resistance in patients with moderate to severe OSA to mitigate the risk of metabolic syndrome and cardiovascular complications. Further large-scale longitudinal studies are recommended to explore causality and potential therapeutic interventions.